Pompey, Cato, and the governance of the Roman Empire - Morrell, Kit (Oxford University Press, 2017)
Leading Romans in the late republic were more concerned about the problems of their empire than is generally recognized. This text challenges the traditional picture by exploring the attempts made at legal and ethical reform in the period 70-50 BC, while also shedding new light on collaboration between Pompey and Cato, two key arbiters of change